STUDI KASUS PEMBUATAN PERMEN JELLY BERBAHAN DASAR KOMBINASI EKSTRAK ETANOL BAYAM MERAH (EEBM) DAN EKSTRAK ETANOL BUNGA KRISAN (EEBK) - Puspadewi, Yuniar Angelia; kusbandiyah, Jiarti; Devyanti, Elva (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2025)
Jelly candy is one of the most popular products because it is made from fruit or vegetables so that it has unique properties and has more nutritional value than other candies. Jelly candy sold in the market generally uses chemical essence ingredients. The ingredients for making jelly candy consist of sugar, pectin and a combination of red spinach ethanol extract and chrysanthemum flower ethanol extract as the basic ingredients so that it has a chewy and elastic texture. This study aims to determine the right composition of the amount of pectin, sugar, drying time in order to produce jelly candy with good quality and nutritional value. This study used a randomized block design (RAK) with organoleptic tests to assess the level of preference or suitability of a product so that it can be accepted by consumers. The study consisted of 4 groups of jelly candy with each group different for the amount of EEBM and EEBK, Sugar, Pectin, and drying time while the temperature for all groups was the same, namely 60ºC. Group 1 (PJF1) consists of EEBM EEBK: 30g, Sugar: 40gr, Pectin: 3gr,, Time: 2 hours. Group 2 (PJF2) consists of EEBM EEBK: 20g, Sugar: 30gr, Pectin: 4gr, Time: 2 hours. Group 3 (PJF3) consists of EEBM EEBK: 15gr, Sugar: 20gr, Pectin: 5gr, Time: 3 hours. Group 4 (PJF4) consists of EEBM EEBK: 10gr, Sugar 10gr, Pectin: 6gr, Time: 3 hours. The results of the study conducted on 12 female teenage panelists showed that to produce jelly candy made from red spinach ethanol extract and chrysanthemum flower ethanol extract that is good and preferred in terms of color, aroma, texture and taste can be made by using 3gr of pectin, 40gr of sugar, temperature 60ºC and drying time 2 hours.